2023
DOI: 10.1021/acsnano.2c11457
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Role of Surfaces in the Deformation of Platinum Nanoparticles

Abstract: The mechanical behavior of nanostructures is known to transition from a Hall-Petch-like “smaller-is-stronger” trend, explained by dislocation starvation, to an inverse Hall-Petch “smaller-is-weaker” trend, typically attributed to the effect of surface diffusion. Yet recent work on platinum nanowires demonstrated the persistence of the smaller-is-stronger behavior down to few-nanometer diameters. Here, we used in situ nanomechanical testing inside of a transmission electron microscope (TEM) to study the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…As the particle size decreases for a specific material, the melting temperature decreases and thermal vibration increases; therefore, surface diffusion will play an increasingly strong role in nucleating dislocations. In addition, prior work by some of the present authors demonstrated both “displacive” and “diffusive” behavior of platinum nanoparticles, with a strong decrease in strength due to decreasing size for the surface-dislocation-nucleation regime (displacive deformation); 52 however, that work, and the others mentioned, could not distinguish the mechanism of the weakening.…”
Section: Introductioncontrasting
confidence: 72%
See 2 more Smart Citations
“…As the particle size decreases for a specific material, the melting temperature decreases and thermal vibration increases; therefore, surface diffusion will play an increasingly strong role in nucleating dislocations. In addition, prior work by some of the present authors demonstrated both “displacive” and “diffusive” behavior of platinum nanoparticles, with a strong decrease in strength due to decreasing size for the surface-dislocation-nucleation regime (displacive deformation); 52 however, that work, and the others mentioned, could not distinguish the mechanism of the weakening.…”
Section: Introductioncontrasting
confidence: 72%
“…For nanostructures, this is often called “diffusive deformation”. Prior work by the present authors using a similar apparatus 52 have explicitly distinguished homogeneous deformation in the “diffusive regime” from heterogeneous deformation in the “displacive regime”, with a transition occurring at approximately 9 nm. Therefore, that prior work, and also prior simulations of the so-called “Coble-creep-like behavior”, 51 confirm that the present 12 and 16 nm nanoparticles should undergo displacive (defect-based) deformation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation